Salmonella enterica Serovar Typhi Possesses a Unique Repertoire of Fimbrial Gene Sequences - Townsend, Stacy M. (American Society for Microbiology, 2001)
Salmonella enterica serotype Typhi differs from nontyphoidal Salmonella serotypes by its strict host adaptation to humans and higher primates. Since fimbriae have been implicated in host adaptation, we investigated whether the serotype Typhi genome contains fimbrial operons which are unique to this pathogen or restricted to typhoidal Salmonella serotypes. This study established for the first time the total number of fimbrial operons present in an individual Salmonella serotype. The serotype Typhi CT18 genome, which has been sequenced by the Typhi Sequencing Group at the Sanger Centre, contained a type IV fimbrial operon, an orthologue of the agf operon, and 12 putative fimbrial operons of the chaperone-usher assembly class. In addition to sef, fim, saf, and tcf, which had been described previously in serotype Typhi, we identified eight new putative chaperone-usher-dependent fimbrial operons, which were termed bcf, sta, stb, ste, std, stc, stg, and sth. Hybridization analysis performed with 16 strains of Salmonella reference collection C and 22 strains of Salmonella reference collection B showed that all eight putative fimbrial operons of serotype Typhi were also present in a number of nontyphoidal Salmonella serotypes. Thus, a simple correlation between host range and the presence of a single fimbrial operon seems at present unlikely. However, the serotype Typhi genome differed from that of all other Salmonella serotypes investigated in that it contained a unique combination of putative fimbrial operons.